Plasma level of ADAMTS-13 in maintenance hemodialysis patients and its relation to arteriovenous fistula thrombosis - Hammadi Fahad, Saja; Ahmed Ameen , Najiha (Diyala Journal of Medicine, 2023)
Background: End-stage renal disease is the final stage of chronic kidney disease in which irreversible deterioration in renal function occur and the body fails to maintain fluid and electrolyte balance, this need regular hemodialysis (HD) a process that removes accumulated solute from a patient with near-total renal function loss. Arteriovenous fistula (AVF) is the vascular access of choice for patients who require hemodialysis. AVF thrombosis is a major issue in hemodialysis patients, which increase their morbidity and lessen HD efficiency. Objective: To assess plasma level of ADAMTS-13 in HD patients and its association with AVF thrombosis, and to correlate the plasma level of ADAMTS-13 with age, duration of dialysis, certain hematological parameters and estimated GFR. Patients and Methods:This Cross_sectional study done on 60 patients with ESRD on regular HD sessions, 20 healthy persons were included as a control . The patients subdivided into two subgroups with and without AVF thrombosis. Plasma samples were freezed until the test for the level of ADAMTS-13 was done. Results: The plasma ADAMTS-13 level was significantly lower in HD patients compared to control group (P < 0.001), and was a significantly lower in patients with a history of AVF thrombosis than HD patients without a history of AVF thrombosis. HD patients with AVF thrombosis had significantly lower eGFR compared to patients without a history of AVF thrombosis. There was a positive correlation of plasma ADAMTS-13 level with the mean of eGFR , platelet count and negative correlation with MPV. Conclusion: Significant differences between HD patients and control regarding eGFR and hematological parameters . Plasma ADAMTS-13 level was significantly lower in patients compared to controls and significantly lower in patients group with AVF thrombosis than HD group without thrombosis.